The electoral consequences of policy-making in coalition governments - Fabio Ellger; Heike Klüver; Anthea Alberto (Research & Politics, 2023)
Does policy-making in coalition governments affect cabinet parties' electoral performance? Previous research shows that about two thirds of all propositions promised in coalition agreements are actually enacted. But does non-compliance with pledges made in the agreement affect subsequent electoral support? Drawing on the literature on performance voting, we expect that non-compliance is punished by voters, but the effect is conditioned by the importance of the issue and by a parties' seniority status within the coalition. To test our argument, we have compiled the new comparative COALITIONPOLICY dataset on the enactment of more than 7000 policy pledges by 217 cabinet parties in 19 Western and Eastern European countries from 2000 to 2015. Across a broad range of models, we find no effect of pledge fulfillment on subsequent electoral performance. If anything, adherence to policy-promises only increases support for the prime minister party. These results have important implications for our understanding of political representation, coalition governance, and electoral competition in multiparty democracies.
Keywords: 320; Coalition government; policy-making; electoral accountability